2018
DOI: 10.1016/j.aim.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

On p-parts of character degrees and conjugacy class sizes of finite groups

Abstract: Let G be a finite group and Irr(G) the set of irreducible complex characters of G. Let ep(G) be the largest integer such that p ep(G) divides χ(1) for some χ ∈ Irr(G). We show that |G : F(G)|p ≤ p kep(G) for a constant k. This settles a conjecture of A. Moretó [17, Conjecture 4].We also study the related problems of the p-parts of conjugacy class sizes of finite groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Corollary C shows that, in fact, |O p ′ ,p (Sol(G))| p is the only factor of |G| p that cannot be bounded in terms of the largest p-part of the character codegrees. The following consequence of Corollary C has a very similar character degree analog (see Corollary B of [12] and Theorem 3.12 of [16]). We need a lemma first.…”
Section: Application To P-parts Of Character Codegreesmentioning
confidence: 78%
See 1 more Smart Citation
“…Corollary C shows that, in fact, |O p ′ ,p (Sol(G))| p is the only factor of |G| p that cannot be bounded in terms of the largest p-part of the character codegrees. The following consequence of Corollary C has a very similar character degree analog (see Corollary B of [12] and Theorem 3.12 of [16]). We need a lemma first.…”
Section: Application To P-parts Of Character Codegreesmentioning
confidence: 78%
“…It was conjectured in [10] that |G : O p (G)| p is bounded in terms of the largest p-part of the character degrees of G. This conjecture was proved for solvable groups in Corollary B of [12] and for arbitrary groups in Theorem A of [16]. The natural question, therefore, is whether such a bound exists if we replace character degrees by character codegrees.…”
Section: Application To P-parts Of Character Codegreesmentioning
confidence: 99%
“…We now state the orbit theorem for p-solvable groups. This result has been proved in [34] but the proof there has some glitch; we take the opportunity to provide a corrected proof here.…”
Section: Notation and Preliminary Resultsmentioning
confidence: 92%
“…For p > 2, Lewis, Navarro, Tiep and Tong-Viet [20] also studied the case when e p (G) = 1 for arbitrary finite groups. The conjecture of Moretó was recently settled by Qian and the second author in [34].…”
Section: Introductionmentioning
confidence: 98%
“…Moretó [12,Conjecture 4] conjectured that log p b(P ) is bounded by some function of e p (G). The conjecture was first proved for solvable groups by Moretó and Wolf using an orbit theorem of solvable linear groups in [13], and later settled by the authors for arbitrary finite groups in [21]. In fact, we showed that log p |G/O p (G)| p is bounded by a linear function of e p (G).…”
Section: Introductionmentioning
confidence: 77%